AlienG2 - An Automated Analysis Tool for Genome-scale Prediction of Horizontal Gene Transfer - Ahmadvand, Ali (East Carolina University, 2013)
This thesis will present a method for predicting Horizontal Gene Transfer (HGT) events through the creation of a web-based application called AlienG2. HGT is the process of genetic exchange between distantly related organisms. The benefits and applications for identifying HGT are numerous and have been studied in depth, as well as the many techniques and related tools for identifying them. Each one of these tools has its own advantages and disadvantages; yet, there is still a need for a tool that may be used practically and that also delivers results in a relatively short turnaround.  AlienG2 consists of the combination of two already established methods, AlienG and PhyloGenie. AlienG is a sequence similarity comparison based tool that assumes that sequence similarity is correlated to phylogenetic relatedness. Although this tool is fast, the accuracy of the result could be improved. On the other hand, however, while PhyloGenie has been developed using phylogenetic techniques and is known to be the most precise technique for identifying HGT, its very long running time makes it practically unusable. In order to create AlienG2 both AlienG and PhyloGenie had to be improved and then combined. As another improvement to make it more easily accessible for its primary users, which are mostly biologists, this tool was created with Web Service architecture and as a web-based application. The results of experiments show drastic improvement in the running time of the tool, making it quite practical.
Keywords: Computer science; AlienG; HGT; PhyloGenie; Prediction; Tool; Bioinformatics; Web applications; Genetic transformation